Analysis of Comfortable Clog Size for Adult Men - Kusuma, Harun Indra; Rizki, Yulizan (International Journal of Education, Information Technology, and Others, 2024)
Take in water at the mosque, wudhu often clogs is useful to protect the footwear, to keep in touch directly with the surface. Unfortunately while using clogs has not based on the size of a man, In this study we take the size of an adult male feet. take size anthropology human foot. Among other sections leg length, foot width, the distance between the heel of the foot is wide, wide heel, foot circumference (widest size), circumference of the shell. Then practice process data to obtain an average, standard deviation, percentiles 0.05 0.50 0.95. Then Practice provide percentile. Percentile is information that gives the average size in each range, percentiles 0.05 gives small size, 0.50 percentile provide medium and 0.95 percentiles provide large size. appropriate that clogs that are used to reach all adult male foot size and comfortable during use. Among them is the use of percentiles 0.95 feet long, wide leg using the percentile 0.95, the distance between the heel with 0.50 feet wide, the width of the heel, foot circumference (widest size) using 0.05 percentile, using the shell circumference 0.50 percentile. Our last repeated desing the form of clogs according to size percentile which has on set.